Misdiagnosed myocarditis in arrhythmogenic cardiomyopathy induced by a homozygous variant of DSG2: a case report - Liu, Xuwei; Zhang, Yue; Li, Wenjuan; Zhang, Qian; Zhou, Letao; Hua, Yimin; Duan, Hongyu; Li, Yifei (Frontiers in Cardiovascular Medicine, 2023)
Background Arrhythmogenic cardiomyopathy (ACM) is an inherited cardiomyopathy that is rarely diagnosed in infants or young children. However, some significant homozygous or compound heterozygous variants contribute to more severe clinical manifestations. In addition, inflammation of the myocardium and ventricular arrhythmia might lead to misdiagnosis with myocarditis. Here, we describe an 8-year-old patient who had been misdiagnosed with myocarditis. Timely genetic sequencing helped to identify this case as ACM induced by a homozygous variant of DSG2. Case presentation The proband of this case was an 8-year-old boy who initially presented with chest pain with an increased level of cardiac Troponin I. In addition, the electrocardiogram revealed multiple premature ventricular beats. Cardiac magnetic resonance revealed myocardial edema in the lateral ventricular wall and apex, indicating localized injuries of the myocardium. The patient was primarily suspected to have acute coronary syndrome or viral myocarditis. Whole-exome sequencing confirmed that the proband had a homozygous variation, c.1592T > G, of the DSG2 gene. This mutation site was regulated by DNA modification, which induced amino acid sequence changes, protein structure effects, and splice site changes. According to MutationTaster and PolyPhen-2 analyses, the variant was considered a disease-causing mutation. Next, we used SWISS-MODEL to illustrate the mutation site of p.F531C. The ensemble variance of p.F531C indicated the free energy changes after the amino acid change. Conclusion In summary, we reported a rare pediatric case initially presenting as myocarditis that transitioned into ACM during follow-up. A homozygous genetic variant of DSG2 was inherited in the proband. This study expanded the clinical feature spectrum of DSG2-associated ACM at an early age. Additionally, the presentation of this case emphasized the difference between homozygous and heterozygous variants of desmosomal genes in disease progression. Genetic sequencing screening could be helpful in distinguishing unexplained myocarditis in children.